Very high energy gamma-ray astronomy - Weekes, Trevor C. (Institute of Physics Pub., 2011)
High energy gamma-ray photons are the prime probes of the relativistic or high-energy universe, populated by black holes, neutron stars, supernovae, quasars, and matter-antimatter annihilations. Through studying the gamma-ray sky, astrophysicists are able to better understand the formation and behavior of these exotic and energetic bodies.